2023
DOI: 10.1021/acs.jpca.3c01792
|View full text |Cite
|
Sign up to set email alerts
|

High-Definition Ion Mobility/Mass Spectrometry with Structural Isotopic Shifts for Nominally Isobaric Isotopologues

Abstract: We had reported the isotopic envelopes in differential IMS (FAIMS) separations depending on the ion structure. However, this new approach to distinguish isomers was constrained by the unit-mass resolution commingling all nominally isobaric isotopologues. Here, we directly couple high-definition FAIMS to ultrahigh-resolution (Orbitrap) MS and employ the resulting platform to explore the FAIMS spectra for isotopic fine structure. The peak shifts therein for isotopologues of halogenated anilines with 15 N and 13 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
(283 reference statements)
0
2
0
Order By: Relevance
“…Numerous small molecule applications have been demonstrated including separation of isomeric glycans, amino acids and peptides, , bile acids, lipids, , and most recently synthetic cannabinoid metabolites . An important consideration for the proposed coupling of high-resolution IM with quantitative clinical analysis is the anticipated arrival time shift for isotopically labeled internal standards relative to their unlabeled equivalents (i.e., isotopologues), based on differences in their reduced mass. Such separations have been observed previously with SLIM for tetraalkylammonium ions, amino acids, and peptide isotopologues, , as well as with other low-field and high-field IM platforms. Williamson et al used a cyclic IMS (cIMS) device to measure structurally specific mass distribution-based isotopic shifts for 25-hydroxyvitamin D3, among other compounds, and interestingly they determined that the previously identified “closed” and “open” conformations had different relative shifts, with the “closed” showing only a 0.17% relative increase in arrival time in comparison with the 0.28% shift for the “open” conformer . Because there is no difference in reduced mass between the conformers, they attributed the arrival time shift to the change in center of mass owing to the position of the 13 C 5 labeling on the end of the molecule; this positioning would be further from the center of mass in the “open” conformer.…”
Section: Introductionmentioning
confidence: 82%
“…Numerous small molecule applications have been demonstrated including separation of isomeric glycans, amino acids and peptides, , bile acids, lipids, , and most recently synthetic cannabinoid metabolites . An important consideration for the proposed coupling of high-resolution IM with quantitative clinical analysis is the anticipated arrival time shift for isotopically labeled internal standards relative to their unlabeled equivalents (i.e., isotopologues), based on differences in their reduced mass. Such separations have been observed previously with SLIM for tetraalkylammonium ions, amino acids, and peptide isotopologues, , as well as with other low-field and high-field IM platforms. Williamson et al used a cyclic IMS (cIMS) device to measure structurally specific mass distribution-based isotopic shifts for 25-hydroxyvitamin D3, among other compounds, and interestingly they determined that the previously identified “closed” and “open” conformations had different relative shifts, with the “closed” showing only a 0.17% relative increase in arrival time in comparison with the 0.28% shift for the “open” conformer . Because there is no difference in reduced mass between the conformers, they attributed the arrival time shift to the change in center of mass owing to the position of the 13 C 5 labeling on the end of the molecule; this positioning would be further from the center of mass in the “open” conformer.…”
Section: Introductionmentioning
confidence: 82%
“…More recently, high-resolution IMS–MS platforms have begun to study the effects of mass distribution (i.e., changes in center of mass, CoM, and moments of inertia, MoI) in the separations of isotopologues and isotopomers. Previous work focused on naturally occurring isotopologues (e.g., 13 C, 37 Cl, and 81 Br) as well as molecules that were derivatized with stable heavy isotopes. It has been demonstrated that these mass distribution-based isotopic shifts can be isomer- and conformer-specific in nature as well as orthogonal to CCS, thus potentially providing analytical utility through a two-dimensional approach for unknown characterization. Additionally, computational work has demonstrated good agreement between simulated rotational effects in IMS–MS and experimental results of mass distribution-based isotopic shifts. , …”
Section: Introductionmentioning
confidence: 99%